2006 Symposium on VLSI Circuits, 2006. Digest of Technical Papers.
DOI: 10.1109/vlsic.2006.1705346
|View full text |Cite
|
Sign up to set email alerts
|

A 6-Bit 800-MS/s Pipelined A/D Converter with Open-Loop Amplifiers

Abstract: A 6-bit 800-MS/s pipelined A/D converter (ADC) achieves SNDR and SFDR of 33.7 dB and 47.5 dB, respectively. Employing voltage-mode open-loop amplifiers in gain stages, global gain control techniques, and two-bank-interleaved architecture, the proposed pipelined A/D converter relaxes stringent design tradeoffs between speed and power. Fabricated in a 0.18-m CMOS technology, the ADC consumes 105 mW from a 1.8-V power supply while the active area is only 0.5 mm 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The resulting sample-rate of 2.4 GS/s is, to the authors' best knowledge, significantly faster than any previously reported single-channel pipeline ADC [1][2] [3].…”
Section: Introductionmentioning
confidence: 83%
“…The resulting sample-rate of 2.4 GS/s is, to the authors' best knowledge, significantly faster than any previously reported single-channel pipeline ADC [1][2] [3].…”
Section: Introductionmentioning
confidence: 83%
“…Gain mismatch should be kept below ±5% to meet target SNDR of 56 dB. A simple differential pair [10] was used as an amplifier and source degeneration has been employed to linearize the amplifier's gain. In addition, the ADC input range is limited well below the supply, i.e., 0.88 V pp to reduce mismatch errors.…”
Section: B Amplifier Gain Mismatch Effect On Interpolationmentioning
confidence: 99%
“…As outlined, there are limitations in obtaining desired performance and the solution can be the attempt to obtain those performance with the evolving technology or to invent new algorithms or new architectures that fit the advantageous feature of the new processes. Since speed is one of the key advantages, methods that trade speed with other paramenters are good candidates for future developments [13][14][15][16][17][18].…”
Section: A New Algorithms and Architecturesmentioning
confidence: 99%